THE IMPACT OF EDUCATIONAL TECHNOLOGY ON THE ACHIEVEMENT IN THE GENERAL SCIENCE SUBJECTS OF THE 6 th GRADE STUDENTS - Abdel-Rahman Arman, Ibrahim Mohd (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to investigate the impact of educational technology (El-Gazzar’s model) on the achievement in the general science subjects of the 6th grade students. The sample of the study consisted of (54) students – males and females – from 6 th grade – Abu Deis Coeducation school. The researcher assigned two groups randomly (control and experimental) group. To achieve the objective of the study, the researcher collected information by using a multiple choice test of (40) items. Students were given pre-test and post. . The test was subjected to validity, reliability, and level of difficulty and discrimination measures The Data were analyzed by using (SPSS) with ANCOVA, the results showed following:- There was a statistically significant difference at the level (α ≤0.05) in achievement of science due to the method of teaching in favor the group which is experimental, There was no statistically significant difference at the level (α ≤0.05) in achievement of science due to the interaction between teaching method and gender. Based on these results the researcher recommends the use of Educational Technology (El-Gazzar’s Model) in teaching and. especially in teaching science, for the purpose of raising the level of students’ achievement. And performing similar studies on other grades, and other units, with larger groups and samples and in several areas in order to generalize the results of this study.